Health in humanitarian emergencies principles and practice for public health and healthcare practitioners - Anderson, Mark; Gerber, Mike; Townes, David (Cambridge University Press, 2018)
The fields of Global Health and Global Emergency Response have attracted increased interest and study. There has been tremendous growth in the educational opportunities around humanitarian emergencies; however, educational resources have not yet followed the same growth. This book corrects this trend, offering a comprehensive single resource dedicated to health in humanitarian emergencies. Providing an introduction to the public health principles of response to humanitarian emergencies, the text also emphasizes the need to coordinate the public health and emergency clinical response within the architecture of the greater response effort. With contributing authors among some of the world's leading health experts and policy influencers in the field, the content is based on best practices, peer reviewed evidence, and expert consensus. The text acts as a resource for clinical and public health practitioners, graduate-level students, and individuals working in response to humanitarian emergencies for government agencies, international agencies, and NGOs.